2011
DOI: 10.3109/17435390.2011.625127
|View full text |Cite
|
Sign up to set email alerts
|

Differential toxicity of copper (II) oxide nanoparticles of similar hydrodynamic diameter on human differentiated intestinal Caco-2 cell monolayers is correlated in part to copper release and shape

Abstract: The potential toxic effects of copper oxide (CuO) nanoparticles (NPs) were studied on differentiated Caco-2 cell monolayers, a classical in vitro model of human small intestine epithelium. Two types of CuO NPs, with different specific surface area, different sizes as raw material but the same hydrodynamic diameter in suspension, differentially disturbed the monolayer integrity, were cytotoxic and triggered an increase of the abundance of several transcripts coding for pro-inflammatory cytokines and chemokines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 49 publications
3
61
0
Order By: Relevance
“…In general, copper-containing NPs show a size-and species-dependent toxicity to organisms (Di Bucchianico et al 2013;Piret et al 2012). For instance, Chen et al (2006) found that CuNPs could induce more severely pathological injuries to the kidney, liver, and spleen of mice compared to copper at micrometer size.…”
Section: Introductionmentioning
confidence: 99%
“…In general, copper-containing NPs show a size-and species-dependent toxicity to organisms (Di Bucchianico et al 2013;Piret et al 2012). For instance, Chen et al (2006) found that CuNPs could induce more severely pathological injuries to the kidney, liver, and spleen of mice compared to copper at micrometer size.…”
Section: Introductionmentioning
confidence: 99%
“…These cells can undergo enterocytic differentiation (Jumarie and Malo 1991;Piret et al 2012) and represent the gastro-intestinal tract in this study. THP-1 cells are monocytes derived from human, male, acute monocytic leukaemia, and can be differentiated into macrophage-like cells (Chanput et al 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To obtain a tight intestinal epithelium, Caco-2 cells were differentiated as described previously (Piret et al 2012). Briefly, 50,000 Caco-2 cells were grown on transwell polycarbonate filters (12 wells, pore diameter of 3 µm, 1.12 cm 2 growth area, Corning Costar) for 16 days.…”
Section: Naïve Caco-2 Cell Line and Differentiated Monolayersmentioning
confidence: 99%
See 2 more Smart Citations